2002
DOI: 10.1093/occmed/52.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Work-related injuries and occupational health and safety factors in smaller enterprises--a prospective study

Abstract: The aim of this study was to determine whether any of the health, environmental and safety (HES) factors registered by visiting small mechanical enterprises in Norway at the start of the study could predict the risk of occupational injuries in subsequent years. Twelve HES factors, including injury awareness, programme for action, employee participation, training and use of personal safety devices, were registered. A questionnaire was completed by interviewing the employer and observing production. Two variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 10 publications
4
34
1
1
Order By: Relevance
“…Studies have identified power presses, metal cutting saws, metalworking lathes, punch presses, and drilling machines as hazardous pieces of equipment [McCann, 1998;Stanbury et al, 2003], although it is not clear how these designations were made. In a study of small business establishments in Norway, Bull et al [2002] linked the lack of protective safety features on machines along with the failure to use personal protective equipment to a twofold increased risk of injuries in small metal working businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified power presses, metal cutting saws, metalworking lathes, punch presses, and drilling machines as hazardous pieces of equipment [McCann, 1998;Stanbury et al, 2003], although it is not clear how these designations were made. In a study of small business establishments in Norway, Bull et al [2002] linked the lack of protective safety features on machines along with the failure to use personal protective equipment to a twofold increased risk of injuries in small metal working businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Bull, Riise and Moen [21]investigated whether any heath, environment and safety (HES) factors registered by organisations through visits at the start of a study could be used to predict the risk of injury in subsequent years. The researchers registered twelve HES factors (including in jury awareness, programme for act ion, emp loyee participation, training and use of personal protective devices(PPDs)) through the use of questionnaires and observations made during production in a sample of two hundred and eighty eight small mechanical enterprises [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers registered twelve HES factors (including in jury awareness, programme for act ion, emp loyee participation, training and use of personal protective devices(PPDs)) through the use of questionnaires and observations made during production in a sample of two hundred and eighty eight small mechanical enterprises [21]. Using regression analysis, the researchers concluded that increasing the use of PPDs and safety equip ment on machines was most likely to increase prevention of injuries, and that frequent inspections with feedback to workers was most effective means of reducing injuries [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…La réticence des patrons de PE en ce qui a trait à la réglementation de tout ordre est bien documentée (Lamm 1997 ;Vickers et coll. 2003 ;Walters 2001) et s'exprime ici en relation avec les normes concernant les machines (Bull, Riise et Moen 2002 ;Fairman et Yapp 2005 ;Walters 2001). Cette fois, ce sont la capacité économique et la survie des entreprises qui sont le plus fortement évoquées, à la fois par les patrons et les employés de PE.…”
Section: La Capacité éConomique Des Peunclassified